2001
DOI: 10.1007/s11746-001-0249-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical binding of jojoba liquid wax to polyethylene

Abstract: Jojoba wax was chemically bonded to polyethylene-in film or hollow fiber form-via a stable sulfonamide bond. The jojoba-bonded polyethylene was obtained by binding allyl amino jojoba derivatives to chlorosulfonated polyethylene. The amount of jojoba added to the polymer ranged from 9 to 98% (w/w), depending on the reaction conditions. Swelling of the polymer in the reaction solvent was the major factor affecting the efficacy of the chemical binding of the jojoba amino groups to the chlorosulfonyl entities of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Jojoba oil produced in Jordan University of Science and Technology showed similar physicochemical properties as those previously reported in the literature ( 35 36 ) indicating its high quality. The surface tension of jojoba oil (33 dyne/cm) is close to the surface tension of human skin (27-28 dyne/cm).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Jojoba oil produced in Jordan University of Science and Technology showed similar physicochemical properties as those previously reported in the literature ( 35 36 ) indicating its high quality. The surface tension of jojoba oil (33 dyne/cm) is close to the surface tension of human skin (27-28 dyne/cm).…”
Section: Discussionsupporting
confidence: 82%
“…The measured acid value, saponification number, iodine number, specific gravity, refractive index, surface tension, and viscosity of the obtained jojoba oil are shown in Table 2 . Jojoba oil produced by Jordan University of Science and Technology had the same physicochemical properties as those previously reported in the literature ( 35 36 ). The values indicated that jojoba oil was of high quality.…”
Section: Resultssupporting
confidence: 75%
“…Low‐density polyethylene (density 0.922g/cm 3 ; thickness 50 μm; melting index 0.3) was purified before use by Soxhlet extraction with hexane. Modified membranes J2NP11 and J2NP12 were prepared as described elsewhere 9. Dioxane (Frutarom) was distilled and dried over NaOH; dimethyl formamide (DMF, 99.8%, Aldrich) was dried over A4 molecular sieves.…”
Section: Methodsmentioning
confidence: 99%
“…By the same token, the modified material in hollow fiber form would be suitable for application in pervaporation processes for separation between polar and nonpolar molecules in pervaporation process. The chemical binding of jojoba liquid wax to chlorosulfonated polyethylene gave a stable polymer, as is described elsewhere 9. The material was prepared by reacting allylic amino jojoba (I, II) with PE–SO 2 Cl via sulfonamide bonds, as illustrated in Scheme .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation